The positioning of Aboriginal students and their languages within Australia's education system: A human rights perspective. (2nd January 2018) - Freeman, Leonard A.; Staley, Bea
Abstract: This paper is a critical review of past and present languages policies in Australian schooling. We highlight the One Literacy movement that contravenes the human rights of Australia's Aboriginal students. This in turn impacts students' right to freedom of opinion and expression as stated in Article 19 of the Universal Declaration of Human Rights. The One Literacy movement operates by equating Standard Australian English literacy acquisition with Australia's global competitiveness and economic success. There is only one pathway through the Australian English curriculum with common assessments and standards. However, the Australian Curriculum provides three distinctive pathways when students from an English-speaking background learn languages other than English. We reveal this double standard, where current educational policies prioritise the languages of trade (e.g. Chinese) and accommodate speakers of these languages. Meanwhile Aboriginal-language-speaking students are not provided with the same accommodations. For educational equity, there should be a distinctive English language learner pathway that recognises that the majority of remote Aboriginal students from the Northern Territory are learning English as an additional language. We advocate for these changes because all children have a right to an appropriate education that will enable them to flourish as learners and citizens.